Enhancing artificial upwelling in stratification-dominated coastal aquaculture - Zou, Zhiyu; Fan, Wei; Zhao, Yonggang; Yue, Lulu; Hu, Shicheng; Chen, Ying (Frontiers in Marine Science, 2025)
Coastal aquaculture faces dual challenges of eutrophication and carbon sequestration inefficiency, particularly in stratified environments where limited water exchange hinders nutrient redistribution. This study investigates air-lift artificial upwelling (AU) as a sustainable solution to enhance water exchange in coastal aquaculture zones, integrating hydrodynamic optimization with ecological benefits. Through theoretical modeling and laboratory experiments, we establish a framework to predict intrusion layer dynamics (trap height hT, thickness L, and flow rate Qi) of AU plumes, validated by controlled flume trials. Field applications in mussel aquaculture demonstrate that optimized AU operation elevates chlorophyll-a (Chl-a) concentrations by 40.2% in the farming layer while reducing energy consumption by 65% compared to AU in crossflow-dominated (CD) environments. By aligning air injection rate with stratification intensity and current velocity, AU amplifies nutrient delivery precision and carbon sequestration through shellfish calcification. These findings highlight AU’s potential to mitigate coastal pollution, support sustainable aquaculture, and advance ocean-based climate solutions.